The course of binge eating from adolescence to young adulthood - Goldschmidt, Andrea B. (2013)
OBJECTIVE: The course of binge eating in adolescence is variable and little is known about factors maintaining binge eating behaviors. The current study sought to characterize the course of binge eating and identify psychosocial factors associated with its maintenance. METHODS: A population-based sample reported on binge eating, depression symptoms, self-esteem, and body satisfaction at 5-year intervals spanning early/middle adolescence [Time 1 (T1)], late adolescence/early young adulthood [Time 2 (T2)] and early/middle young adulthood [Time 3 (T3)]. Logistic regression examined factors predicting maintenance or cessation of binge eating. RESULTS: A total of 15.8% of participants with binge eating at T1 continued to report binge eating at T2, and 42.0% of participants with binge eating at T2 continued to report binge eating at T3. From T1 to T2, improvements in self-esteem predicted cessation of binge eating. From T2 to T3, cessation of binge eating was predicted by improved body satisfaction, greater decreases in depression symptoms, and greater improvements in self-esteem. CONCLUSIONS: Binge eating is relatively stable from late adolescence/early young adulthood to early/middle young adulthood, but less so from middle/late adolescence to late adolescence/early young adulthood. Improvements in psychosocial functioning during this timeframe may improve the outcome of binge eating, although mechanisms responsible for psychosocial changes (e.g., treatment involvement) require further investigation. Self-esteem appears to be a particularly salient factor involved in binge eating cessation and should be targeted in prevention and treatment programs.